Alternative paradigms for sustainability: the Māori worldview. (6th March 2020) - Kennedy, Ann-Marie; McGouran, Cathy; Kemper, Joya A.
Abstract : Purpose: The authors do not claim that the following represents the views of any one tribe but instead the culmination of the academic literature written on the topic. Marketing's current Western dominant social paradigm (DSP) is said to perpetuate "green", yet unsustainable practices. The DSP does not support strictly pro-environmental practices and its proposed alternative, the new environmental paradigm (NEP), lacks in-depth conceptualisation, especially concerning business and marketing activities. However, the two paradigms contrast so much that a shift from one to the other is vehemently argued against and conceptually rife with problems. This paper aims to expand upon the merits of the NEP using indigenous people's environmental philosophies – specifically the Māori people of New Zealand[1 ] – as examples of historically supported and successful sustainable philosophies. It conceptualises the Māori view to provide a more practical alternative to the DSP and includes propositions for marketing implementation of this perspective. Findings: By explicating both the DSP and NEP and reflecting on each through an indigenous Māori view, this paper provides propositions for a broadened paradigm that supports sustainability and its application for sustainable marketing. Research limitations/implications: The implications of this research are in the area of paradigm development and in providing an alternative paradigm to that of the DSP. This paper is the first to fully explicate parts of the NEP and considers a solution to the problems of changing the current DSP so drastically by broadening the NEP using a Māori worldview. Practical implications: The propositions and examples provided in this work give practical application of the newly presented paradigm for marketers influenced by indigenous belief systems. Originality/value: This paper is the first to explicate parts of the NEP and broaden its reach by integrating a Māori worldview as an alternative to drastically changing the current DSP. It does so by proposing that marketers embrace a middle ground that is influenced by indigenous belief systems.